Company Dividend Policy Analysis Compass Index 100 In Indonesia Stock Exchange - Rio Setiono Nugroho; Siti Hidayati (Budapest International Research and Critics University, 2022)
The purpose of the study was to see the effect of leverage as proxied by Debt to Equity Ratio (DER), profitability as proxied by Return on Equity (ROE), and company size proxied by the natural logarithm of total assets (SIZE) on Dividend Policy proxied by Dividend Payout Ratio (DPR). The population of this study is the Kompas 100 Index Company on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. In determining the sample in this study, purposive sampling technique was used and obtained 44 companies with the Kompas 100 Index and an observation period of four years, so that 176 sample data were obtained. Data analysis used the Microsoft Excel 2019 application and E-views version 12 to test the hypothesis with panel data regression analysis with a significance level of 5%. The results of the study partially show that, (1) Leverage has no effect on Dividend Policy, (2) Profitability has an effect on Dividend Policy, and (3) Company Size has no effect on Dividend Policy.